KEPASTIAN HUKUM AKTA PERDAMAIAN DALAM PENYELESAIAN SENGKETA TUMPANG TINDIH HAK ULAYAT DENGAN TANAH SERTIPIKAT. - Dewanto, Bisma Aryo; Hutomo, Putra; Widyanti, Amelia Nur (LPPM Institut Pendidikan Nusantara Global, 2024)
Violations of the indigenous peoples' rights to customary land ownership recognized by the state often fail to provide justice and legal certainty to the indigenous communities. For instance, the customary land dispute between the Mansim indigenous community and a third party has yet to find a resolution and offer legal certainty to the parties involved, despite the dispute having gone through judicial settlement. The legal theories applied here include legal certainty and dispute resolution. The method used in this study is normative juridical legal research, conducted by examining library materials or secondary data only, supported by interviews. The approaches in this study include the legislative approach, the conceptual approach, the analytical approach, and the case approach. The sources of legal material in this study are primary, secondary, and tertiary legal sources, with the collection technique involving the identification and inventory of positive legal rules, examination of library materials, and analysis of legal material sources through systematic and analogous legal interpretation.The findings of the study include that the resolution of overlapping customary land disputes with third parties, based on the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Regulation No. 21 of 2020 concerning the Handling and Settlement of Land Cases, can begin with a mediation process. Mediation is implemented in the dispute between the Mansim indigenous community and a third party, using the Yielding and Problem-Solving strategy approach. The legal certainty of the peace deed, which is an authentic act in the context of resolving overlapping customary rights with certificated land, has the binding legal force and becomes the law for those who execute the agreement